EFEKTIFITAS STRATEGI PEMASARAN TAMAN PINTAR YOGYAKARTA DI ERA PANDEMI COVID-19 - Sariyani, Sariyani; Damayanti, Dila (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
Colvild l1l9 palndlemlic lthlatl oclculrrledl alt lthle elndl olfl 2l01l9 which not only hladl an ilmplaclt on the world but also in Indonesia. Olnel olf lthlel tourist destinations that has experienced a very drastic decline is the Yogyakarta Smart Park. Taman Pintar Yogyakarta is an educational tourism vehicle destination lolcalteld lin tlhel clenltelr olf tlhel clitlyl olf Yogyakarta. Tlhle alpplrolaclh lusledl iln tlhils sltuldyl ils lal qluallitlatilvel alpprloalchl. Dlatla colllelctiloln telchlniqluels ulseld iln tlhils research include documentation techniques, interviews, observation and literature studies. lThle daltal anlallysils telchnliqluel ulseld lbly rleslearlchelrls luslesl tlhel Millels alndl Hulbelrmlanl moldell. Efforts made bly tlhel management of Taman Pintar Yogyakarta so that it can run effectively during the Covid-19 pandemic include carrying out internal and external activities, implementing health protocols, conducting counseling for employees. Yogyakarta Smart Park's strategy for dealing with the Covid-19 pandemic includes preparing SOPs, providing facilities and infrastructure, simulations and limited opening trials. The marketing strategies implemented by Taman Pintar Yogyakarta are plrilcel stlratlegyl, plrolmotliolnl sltrlatelgyl, pllalcle sltrlatlegyl alndl plroldulctl sltrlatleglyl.